A simulation study on strength and fatigue analysis of hydraulic excavator buckets - Pan, Wenbin (Frontiers in Mechanical Engineering, 2025)
The bucket of industrial hydraulic excavator is one of the key components in the excavator. Considering the poor model construction ability of the current bucket strength and fatigue simulation method of industrial hydraulic excavator, which leads to the large difference between the simulation results and the measured results, a new bucket strength and fatigue simulation method of industrial hydraulic excavator is designed. The parametric design of bucket of industrial hydraulic excavator is completed by using ADAMS/View technology. Referring to the actual digging force of the bucket, the bucket strength of industrial hydraulic excavator is simulated. The cumulative fatigue damage reliability analysis algorithm is used for bucket fatigue simulation, and the simulation results are statistically analyzed. The experimental results show that the simulation results of the method are closer to the measured results, the relative error is controlled within 5%, and the computational efficiency is improved by about 80% compared with the traditional method. The method provides a new technical means for the design and optimization of hydraulic excavator bucket, which has high application value.